Unpacking the Impact of Digital Touchpoint Excellence and Switching Resilience on Building Millennial Loyalty and Financial Decision-Making at Phintraco Sekuritas - Hapsari, Ayuningtyas Yuli; Anwar, Tezza Adriansyah; Sugiana, Neng Susi Susilawati; Widjatun, Vincentia Wahju; Padmanegara, Oliver Hasan (Communication In Research And Publications, 2025)
The purpose of this study is to investigate the influence of Digital Touchpoint Excellence and Switching Resilience on Millennial Loyalty and Financial Decision-Making in the context of digital investment services at Phintraco Sekuritas. In particular, the study seeks to understand how high quality digital interactions and user resilience contribute to sustained loyalty among millennials in Java and Bali. A quantitative research method was employed using a structured online questionnaire distributed to millennial respondents aged 20–40 who actively use digital investment platforms. A sample of 384 respondents was selected through proportional random sampling across major cities in Java and Bali. The data were analyzed using Structural Equation Modeling (SEM) with AMOS to test the relationships among variables. The results reveal that Digital Touchpoint Excellence significantly influences both Financial Decision-Making and Millennial Loyalty, with Financial Decision-Making acting as a partial mediator. Furthermore, Switching Resilience strengthens the impact of Financial Decision-Making on Millennial Loyalty, indicating its role as a moderating variable. The findings suggest that creating seamless, personalized, and reliable digital touchpoints is crucial in enhancing user confidence in financial decisions, which in turn drives loyalty. This study provides practical implications for fintech service providers, emphasizing the importance of investing in digital customer experiences and resilience-building strategies to retain millennial users. Uniqueness of this study lies in its integrated approach that combines psychological resilience and digital UX excellence within a financial decision-making context, specifically targeting millennial behavior in the Indonesian capital market a perspective that remains underexplored in previous research.